Implications of N-terminal pro-B-type natriuretic peptide in patients with three-vessel disease. (24th June 2019) - Zhang, Ce; Jiang, Lin; Xu, Lianjun; Tian, Jian; Liu, Junhao; Zhao, Xueyan; Feng, Xinxing; Wang, Dong; Zhang, Yin; Sun, Kai; Xu, Bo; Zhao, Wei; et al.
Abstract: Aims: Risk assessment and treatment stratification for three-vessel disease (3VD) remain challenging. N-terminal pro-B-type natriuretic peptide (NT-proBNP) is an established biomarker for prognostication and treatment in heart failure. The present study aimed to evaluate the prognostic value of NT-proBNP beyond the SYNTAX score II (SSII), and its association with long-term outcome after three strategies [percutaneous coronary intervention (PCI), coronary artery bypass grafting (CABG), and medical therapy (MT)] in a cohort of patients with 3VD. Methods and results: A total of 6597 patients with available baseline NT-proBNP data were included in the study. Baseline, procedural, and follow-up data were collected. The primary endpoint was all-cause death. Secondary endpoints included cardiac death and major adverse cardiac and cerebrovascular events (MACCE), a composite of death, myocardial infarction, and stroke. During a median follow-up of 7.0 years, higher NT-proBNP levels were strongly associated with increased risks of all-cause death, cardiac death, and MACCE (all adjusted P  < 0.01). Moreover, NT-proBNP significantly improved discrimination and reclassification of the SSII. Notably, there was a significant interaction between NT-proBNP quartiles and treatment strategies for MACCE ( P  = 0.004). Revascularization was associated with lower risks of MACCE than MT, except for patients in the lowest quartile wherein no such association was observed. Among patients in the highest quartile, PCI was associated with an increased risk of MACCE compared with CABG (hazard ratio 1.43, 95% confidence interval 1.09–1.87). Conclusion: N-terminal pro-BNP is a potential biomarker for risk stratification and therapeutic decision-making in patients with 3VD. Further randomized studies are needed to confirm these findings.